Crocodile ride: first reading fun - Harker, Jillian; Smith, Jan (Autumn Pub. Chichester, 2010)
This fun story follows a cheeky crocodile who takes readers on a wild ride through the jungle. As he encounters various animals, the tale combines adventure and playful rhymes, encouraging children to join in the excitement. The vibrant illustrations and lively narrative make it an engaging read for young adventurers.